Perioperative versus postoperative chemotherapy for gastric cancer: A propensity score matched analysis. Issue 5 (28th July 2020) - Kumar, Surendra; Seshadri, Ramakrishnan Ayloor; Trivadi, S. Ganesan; Dhanushkodi, Manikandan; Ellusamy, Hemanth Raj
Abstract: Aim: In advanced gastric cancer, chemotherapy, given either perioperatively or as an adjuvant treatment, has been shown to improve survival when compared to surgery alone. However, no trial has compared these two approaches head‐to‐head. Hence, we aimed to compare the short‐ and long‐term outcomes of patients with gastric cancer who received either perioperative chemotherapy or adjuvant chemotherapy. Methods: Retrospective analysis of patients with gastric cancers treated from 2010 to 2016. Using propensity score matching, resected patients who received perioperative chemotherapy were matched for histology, nodal dissection, and extent of surgery with another cohort of patients who received only adjuvant chemotherapy to create two matched groups of 101 patients each—group A (perioperative) and group B (adjuvant)—and the outcomes were compared between them. Results: The patient demographics were evenly distributed in the two groups. There was no difference in the median number of chemotherapy cycles delivered (6 vs 6, P  = .8) or the grade 3‐4 toxicity (17.2% vs 12.1%, P  = .26) in group A and group B, respectively. We could not demonstrate a significant difference in the postoperative mortality (2.6% vs 0%) or overall postoperative complications (23% vs 19%) between groups A and B. The overall recurrence rate (37% vs 42%), 3‐year disease‐free survival rate (51% vs 48%), and 3‐year overall survival rate (53% vs 55%) were not significantly different in group A and group B, respectively. Conclusions: We were unable to detect a significant difference in the short‐term or long‐term outcomes of patients with gastric cancer undergoing either perioperative or adjuvant chemotherapy.